Exploring the Mechanisms of Anti‐Aβ42 Aggregation Activity of Walnut‐derived Peptides using Transcriptomics and Proteomics in vitro. Issue 5 (11th January 2022) - Wang, Min; Gong, Congcong; Amakye, William Kwame; Ren, Jiaoyan
Abstract : Inhibiting β ‐amyloid (A β ) aggregation is of significance in finding potential candidates for Alzheimer's disease (AD) treatment. Accumulating evidence suggests that nutrition is important for improving cognition and reducing AD risk. Walnut has been widely used as a functional food for brain health; however the underlying mechanisms remain unknown. Here, we investigated the molecular level alteration in Arctic mutant A β 42 induced aggregation cell model by RNA‐seq and iTRAQ approaches after walnut‐derived peptides Pro‐Pro‐Lys‐Asn‐Trp (PW5) and Trp‐Pro‐Pro‐Lys‐Asn (WN5) interventions. PW5 or WN5 could significantly decrease abnormal A β 42 aggregates. However, resultant alterations in transcriptome (substantially unchanged) were inconsistent with proteomic data (marked change). Proteomic analysis revealed 184 and 194 differentially expressed proteins unique to PW5 and WN5 treatment, respectively, for inhibiting A β 42 protein production or increasing protein degradation via the mismatch repair pathways. Our study provides new insights into the effectiveness of food‐derived peptides for anti‐A β 42 aggregation in AD.